Legal protection of elderly persons and risk of their victimization by criminal acts with elements of domestic violence - Mirić Filip (Temida, 2012)
The aging process is inevitable. It follows the individual from birth until death. Due to the inability of people to influence it, there is a greater obligation of society to provide the people in the „third age“ a dignified life, without any form of victimization. The author defines which people are considered old according to positive legal acts of the Republic of Serbia. The subject of this paper are the factors that increase the risk of victimization of the elderly within the family, taking into account the physical, psychological, sexual and economic violence against the elderly, as well as mechanisms for their legal protection from domestic violence, as one of the most effective tools of the state and society in general for protection of this particularly vulnerable social group. Relevant provisions of the Criminal Code and the Code of Criminal Procedure of the Republic of Serbia with a critical analysis of the incrimination of offenses with elements of domestic violence where the victim is usually an old person will be analyzed. From the subject defined in this manner, stems the paper‘ s mainly descriptive goal of describing the phenomenon through the analysis of the major forms of violence to which the elderly within the family are exposed (physical, psychological, economic and sexual violence). The purpose of the paper is also to analyze the factors that increase the risk of victimization of the elderly and the mechanisms for their legal protection from domestic violence, point out the harm of this type of violence and thus contribute to combating this negative social phenomenon.